A Comparative Study on Financial Performance of Selected Public & Private Sector Banks in India - Balaji, Ch; Kumar, G. Praveen (Journal of Commerce and Trade, 2016)
Banks form a fundamental component of the financial system and are also active players in financial markets. An efficient banking system capable of mobilizing the savings and channeling them to productive purposes are essential for the development of any economy. The objective of the study is to analyze and compare the overall financial performance of selected public and private sector banks in India. The study is based on secondary data that has been collected from annual reports of the respective banks, Reserve Bank of India website. This research study covers a period of five years i.e. from financial year 2011-2012 to 2015-2016. A quota sample method is used for to select ten banks i.e. five from public sector and five from private sector has been selected and the criteria is based on highest market capitalization generated by banks during 2015-2016. T Test, mean and graphs are used to analyze the data. Although there was increase in profitability for both sector banks the rate of growth is higher for private sector banks. Public sector banks are lagging in many financial parameters and they are facing many challenges also. It is concluded that Public sector banks must redefine their strategies by considering their strengths and weakness and the type of market they are operating.